2021
DOI: 10.3171/2021.6.focus21284
|View full text |Cite
|
Sign up to set email alerts
|

Experimental animal models for moyamoya disease and treatment: a pathogenesis-oriented scoping review

Abstract: OBJECTIVE Moyamoya disease (MMD) is an intracranial steno-occlusive pathology characterized by progressive narrowing of proximal large vessels, including the terminal internal carotid arteries (ICAs), middle cerebral arteries, or anterior cerebral arteries. Named for the “puff of smoke” appearance of the anomalous vascularization visualized on cerebral angiography, MMD lacks a well-defined etiology, although significant insights have been made, including the identification of a susceptibility gene, RNF213, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…However, owing to the unclear mechanism of MMD, there is a lack of effective drugs to prevent its progression, as well as effective Frontiers in Genetics frontiersin.org animal models (Rallo et al, 2021;Ihara et al, 2022). Although some biological targets have recently been identified by genomics, proteomics, or other methods, animal modeling and drug research based on these targets have achieved unsatisfactory results (Rallo et al, 2021;Ihara et al, 2022). This suggests that other mechanisms may be involved in MMD development.…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the unclear mechanism of MMD, there is a lack of effective drugs to prevent its progression, as well as effective Frontiers in Genetics frontiersin.org animal models (Rallo et al, 2021;Ihara et al, 2022). Although some biological targets have recently been identified by genomics, proteomics, or other methods, animal modeling and drug research based on these targets have achieved unsatisfactory results (Rallo et al, 2021;Ihara et al, 2022). This suggests that other mechanisms may be involved in MMD development.…”
Section: Discussionmentioning
confidence: 99%
“…We constructed a cell model of moyamoya disease using serum stimulation to verify the function of the above metabolites. 6 The apoptotic ratios of HBVSMCs in the ischaemic and haemorrhagic subgroups were significantly lower than HC (Figure 2A,B). Cell viability was significantly increased in three MMD groups.…”
mentioning
confidence: 89%
“…7 So far, due to its unknown pathogenesis, no model accurately summarizes the pathological changes in vascular intimal hyperplasia in MMD. 8,9 Recent studies of the DIAPH1 gene mutation in patients of European ancestry have raised the possibility that actin remodeling may be involved in the pathogenesis of MMD, but no specific studies have been performed to test this hypothesis. 10 Proteomic analysis of exosomes from hemorrhagic MMD has suggested that altered expression levels of the actin proteins cofilin and ARP2/3 are involved in the cell cycle of these patients compared with healthy controls.…”
mentioning
confidence: 99%
“…7 So far, due to its unknown pathogenesis, no model accurately summarizes the pathological changes in vascular intimal hyperplasia in MMD. 8,9…”
mentioning
confidence: 99%